(3EJMGa CTQa GdedG HHYV CNHGQ GdQHGW hSdGs - (3eMeO Hf Ydj GdOcGdj GdSdGhj, GdOcGdjs ((3GdMGL CMeO Hf Gdjefj GdfGUQi GdQHGWj s)
(3ChdgG (B:s
(3jbhd QGLj QMeI Gdehdi GdYdj eMeO GdSdGhi hgh GHf Ydi hbO fXeJ QLRkG eHJc````QkG HebUO HYjO dcd ef OQi ai Ld CNHGQ GdQHGW hS```dG hMGd ef ZjQ ajgG ef HdG s
(3BNQgG (B:s
(3hgG CfG Pjdg eTZ````hd YSj jfGd GdbUO hGdeCehd ef hSd Cgd GdYUQ HGdSHGb HMSf hUa hGfJgGA haGb QGeJ Ydi GdYHO CjGOj QH`g ehUhdI aj HYOg hbQHg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(11 (3O(B) s
Keywords: (3GdJGQjNs